A Review of Medicinal Herbs Capable of Preventing Blood Coagulation and Platelet Aggregation - Hossein Elyasi; Hadis Rahimi; Ali Asghar Kiani * (Lorestan University of Medical Sciences, 2018)
Blood coagulation is a process carried out to prevent blood loss when a person is wounded. The blood coagulates in the wound place and creates a barrier which prevents bleeding. The blood coagulation process is one of the most important and vital physiological processes in the human body which is affected by many factors. Many congenital and acquired defects in each of these factors can affect the coagulation process and cause many problems for humans. Related articles were searched from Google Scholar, PubMed, Science Direct, High Wire, MD Consult and Scopus data bases, and finally 19 articles were included in this study. In this study, 19 anti-coagulant medicinal plants were diagnosed and evaluated. Finally, it follows from this study that there are many medicinal herbs that have different effective substances to prevent blood coagulation by various mechanisms. These plants can be used as highly efficient resources in the production of valuable drugs against diseases caused by blood coagulation.